Reprioritizing Research Activity for the Post-Antibiotic Era: Ethical, Legal, and Social Considerations - Hey, Spencer Phillips (The Hastings Center report, 2017)
Many hold that the so-called golden era of antibiotic discovery has passed, leaving only a limited clinical pipeline for new antibiotics. A logical conclusion of such arguments is that we need to reform the current system of antibiotic drug research—including clinical trials and regulatory requirements—to spur activity in discovery and development. The United States Congress in the past few years has debated a number of bills to address this crisis, including the 2012 Generating Antibiotic Incentives Now Act and the 2016 21st Century Cures Act. Experts have also sought to advance antibiotic development by encouraging greater use of trials with noninferiority hypotheses, which are thought to be easier to conduct. The goal underlying these proposals is to stave off the post-antibiotic era by expanding the pharmaceutical armamentarium as quickly as possible. But although new antibiotic agents are necessary to combat the long-term threat of drug-resistant disease, we argue that these research policies, which effectively lower the bar for antibiotic approval, are ethically problematic. Rather, given broader public health considerations related to the full lifecycle of antibiotic use—including development of resistance—we should reject an overly permissive approach to new antibiotic approval and instead set the bar for regulatory approval at a point that will naturally direct research resources toward the most transformative chemical or social interventions.